The Phonological Analysis of Animal Sounds in English and Indonesians - Candra Alim Tohari; Ahmad Idris Asmarandhani; Wijayadi - (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2016)
People in different countries have their own methods on how they imitate the sounds of the same animals. The real example is that Englishmen imitate the sound of cat as /miËËˆaÊŠ/. On the other hand, Indonesians imitate the sound of the same cat as /meÉ”Å‹/. Those sound, in term of linguistics, are considered as onomatopoeic words. This study is about animal onomatopoeic word where the objective of the study is to find both the similarities and differences between how Englishmen and Indonesians imitate the sound of the same animal in term of phonetic features. To achieve the objective of the study, the writer compiles list of twenty animal onomatopoeic words both from English and Indonesian languages. Then the sounds are analyzed in terms of phonetic and phonological theories. As the result, there are similarities as well as differences in both consonants and vowels.